The formation of constructions of floating composite structures for transportation and storage of radioactive cargo - Казимиренко, Юлия Алексеевна (Technology audit and production reserves, 2014)
The patterns and technological recommendations on the formation of multilayer biological protection for floating objects, performing the function of overload and temporary storage of radioactive cargo of low and intermediate level are discussed. The purpose of the article is development of science-based practical recommendations for the development of protective structures with using of new materials. The mechanism of multiple internal reflection of radiation absorption in a heterogeneous environment is fundamental in the design. This mechanism is created by the introduction of the composite layer of hollow glass microspheres, powders of sodium silicate and plumbiferous glasses. The results are based on established patterns in the interaction of ionizing radiation of cargo with materials of constructions and include the selection of compositions and methods for forming of new materials and coatings on their surfaces. The basis of the design of protective constructions of floating structures is new scientific understanding of the processes and mechanisms of interaction of ionizing radiation of transported cargo with new materials of constructions. The research results can be applied in the design of specialized vessels, floating structures and other equipment for the transport and storage of radioactive cargo.